Sistem Pendukung Keputusan Pemilihan Guru Terbaik Menggunakan Metode Waspas di SDN Lenggahsari 03 - Arif Susilo; Nurjanah (DPPM Universitas Pelita Bangsa, 2025)
This study aims to address issues in selecting the best teacher at SD Negeri Lenggahsari 03, where the process was previously conducted manually and was prone to errors and nepotism. The existing selection process lacked objective, criteria-based assessment, highlighting the need for a decision support system to ensure fairness and transparency. The research applies the Weighted Aggregated Sum Product Assessment (WASPAS) method to rank candidates based on predefined criteria, including attendance, certification, years of service, teaching quality, and educational background. The WASPAS method combines weighted sum and weighted product approaches to generate a final score (Qi), providing a more accurate evaluation of alternatives. The results indicate that alternative A1, Ali, S.Pd, achieved the highest final score (Qi) of 1 and was therefore selected as the best teacher. The implementation of the WASPAS-based decision support system proves effective in improving objectivity, transparency, and accuracy in the teacher selection process at SD Negeri Lenggahsari 03.